An exploratory study of the experiences of youth transitioning out of Child and Youth Care Centres in Cape Town to independent adult living - Fredericks, Chanel (Department of Social Development, 2020)
Every year youth living in child and youth care centres (CYCCs) in Cape Town prepare themselves for independent adult living as they approach the age of majority, eighteen years of age, which enables them to legally leave state care. This research study explored the experiences of Cape Town youth transitioning from CYCCs to independent adult living. The study was conducted with a sample of twenty youth from five different CYCCs in Cape Town, South Africa. The study adopted a qualitative approach using a semi-structured interview schedule for face-to-face interviews with the participants. A purposive sample was used for the selection of participants for this study. Data collected during this study was analysed using Tesch’s eight-step approach to data analysis. The study findings revealed that participants had various perceptions regarding their transition from their CYCCs to independent adult living. Some perceived their exit from state care as a disturbance in their lives which resulted in them experiencing a range of emotions such as fear and anxiety as they anticipated how their lives would change once they leave state care. Others recognised that during this time they would experience some independence which meant taking on more responsibility for their lives such as being accountable for their daily living costs which include groceries, electricity and transport. Participants also viewed this transitional period as a time to actively look for alternative accommodation before leaving state care to avoid potential homelessness. Living in care was also understood as an opportunity for youth to successfully complete their high schooling without any disruptions. In addition to this the study findings revealed that participants had aspirations that they hoped to see come to fruition while they prepare for independent adult living. These included making contact with their families of origin, enrolling into tertiary institutions, finding employment and helping others in need. They also foresaw challenges that may arise while they prepared for independent adult living. These challenges included repetition of negative past behaviours, struggling to find employment, worries about safety, worries about not having support after leaving care and possible financial challenges. The study findings also revealed how youth living in CYCCs can be better supported during their transition to independent adult living. This can occur through improving existing transitional programmes, assigning youth living in CYCCs with mentors during their transitional period and improving the government’s role in supporting CYCCs and youth leaving care by, amongst other things, creating more employment opportunities for youth. The main recommendations of the study include that CYCCs provide youth preparing to leave care for independent adult living with the necessary emotional support such as individual counselling sessions where they can disclose and deal with their fears and anxieties about leaving state care. It is also recommended that CYCCs continue to push their education agenda with youth preparing to leave state care so that they can continue to be ambitious when it comes to furthering their education. Another recommendation is that CYCCs readily support youth wanting to make contact with their family of origin during their transition to independent adult living. Finally, children living in CYCCs should be introduced to transitional programmes soon after their entrance into the CYCC programme rather than too close to their exit from state care.